2009
DOI: 10.1021/jp8112478
|View full text |Cite
|
Sign up to set email alerts
|

Hg Binding on Pd Binary Alloys and Overlays

Abstract: The vast majority of the mercury released from coal combustion is elemental mercury. Noble metals such as Pd, Au, Ag, and Cu have been proposed to capture elemental mercury. Density functional theory calculations are carried out to investigate mercury interactions with Pd binary alloys and overlays in addition to pure Pd, Au, Ag, and Cu surfaces using a projected augmented wave method with the Perdew-Wang generalized gradient approximation. It has been determined that Pd has the highest mercury binding energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…Sasmaz et al . studied the adsorption of Hg on Pd binary alloys and overlays using PW91 functionally 25 . They found that Pd has the highest mercury binding energy in comparison to other noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…Sasmaz et al . studied the adsorption of Hg on Pd binary alloys and overlays using PW91 functionally 25 . They found that Pd has the highest mercury binding energy in comparison to other noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of theoretical calculations, many researchers 17,21,22 investigated adsorption of elemental Hg on noble metal clusters theoretically. However, to the best of our knowledge, all studies of elemental Hg adsorption are on larger clusters or the 111 and 001 surfaces of noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…Hg 0 removal with Fe(VI) is a heterogeneous reaction process, in which temperature plays an important role in both Hg 0 diffusion and Hg binding on the metals [30]. Fig.…”
Section: Reaction Temperaturementioning
confidence: 99%